Natural killer cell-based adoptive immunotherapy eradicates and drives differentiation of chemoresistant bladder cancer stem-like cells. Issue 1 (December 2016) - Ferreira-Teixeira, Margarida; Paiva-Oliveira, Daniela; Parada, Belmiro; Alves, Vera; Sousa, Vitor; Chijioke, Obinna; Münz, Christian; Reis, Flávio; Rodrigues-Santos, Paulo; Gomes, Célia
Abstract Background High-grade non-muscle invasive bladder cancer (NMIBC) has a high risk of recurrence and progression to muscle-invasive forms, which seems to be largely related to the presence of tumorigenic stem-like cell populations that are refractory to conventional therapies. Here, we evaluated the therapeutic potential of Natural Killer (NK) cell-based adoptive immunotherapy against chemoresistant bladder cancer stem-like cells (CSCs) in a pre-clinical relevant model, using NK cells from healthy donors and NMIBC patients. Methods Cytokine-activated NK cells from healthy donors and from high-grade NMIBC patients were phenotypically characterized and assayed in vitro against stem-like and bulk differentiated bladder cancer cells. Stem-like cells were isolated from two bladder cancer cell lines using the sphere-forming assay. The in vivo therapeutic efficacy was evaluated in mice bearing a CSC-induced orthotopic bladder cancer. Animals were treated by intravesical instillation of interleukin-activated NK cells. Tumor response was evaluated longitudinally by non-invasive bioluminescence imaging. Results NK cells from healthy donors upon activation with IL-2 and IL-15 kills indiscriminately both stem-like and differentiated tumor cells via stress ligand recognition. In addition to cell killing, NK cells shifted CSCs towards a more differentiated phenotype, rendering them more susceptible to cisplatin, highlighting the benefits of a possible combined therapy. On the contrary, NK cells from NMIBC patients displayed a low density on NK cytotoxicity receptors, adhesion molecules and a more immature phenotype, losing their ability to kill and drive differentiation of CSCs. The local administration, via the transurethral route, of activated NK cells from healthy donors provides an efficient tumor infiltration and a subsequent robust tumoricidal activity against bladder cancer with high selective cytolytic activity against CSCs, leading to a dramatic reduction in tumor burden from 80 % to complete remission. Conclusion Although pre-clinical, our results strongly suggest that an immunotherapeutic strategy using allogeneic activated NK cells from healthy donors is effective and should be exploited as a complementary therapeutic strategy in high-risk NMIBC patients to prevent tumor recurrence and progression.